CATCH AND EFFORT INFORMATION FOR ALBACORE TUNA (THUNNUS ALALUNGA) BY INDONESIA’S LONGLINERS OPERATING FROM BENOA - Lilis Sadiyah; Budi Nugraha; Agustinus Anung Widodo (Research Center for Fisheries, 2013)
Albacore (Thunnus alalunga - ALB) catch was the second highest tuna landed at Benoa Fishing Port and they are mostly landed as frozen bycatch. This paper attempts to provide information on ALB catch and effort trends by Benoa based longline vessels collected by the Benoa Port-based Catch Monitoring and Scientific Observer Programs. The ALB catch landed at the Benoa Fishing Port in 2010 was estimated by the Research Institute for Tuna Fisheries (RITF) to be about 983.14 tons, whereas based on the Indonesian Tuna Long Line Association (ATLI), ALB catch landed at Benoa Fishing Port in 2010 amounted of 2,715.42 tons. This discrepancy was due to sampling for frozen catch (including ALB) could not be conducted in some companies and also there was one company that sell their catch direct to the collector. The observed longline sets were concentrated within the area between 10° - 20°S and 105° - 120°E. Since 2008, the observed setting positions have never extended to south of 20°S. The higher catch rates of ALB were in area south of 15°S.